Respostas

2014-03-24T17:46:08-03:00
É letra b ta certo.

tgx = senx / cosx

senx / cosx = 2

senx = 2*cosx
_____________________

2*cosx / 3*senx

2*cosx / 3*2*cosx

2*cosx / 6*cosx

1/3


1 3 1
2014-03-24T17:50:19-03:00
Tg x = 2 

Você sabe que: tg x =  \frac{senx}{cosx}

Nesta situação você tem que: 

 \frac{2cosx}{3senx} =  \frac{2}{3} . \frac{cosx}{senx} =  \frac{2}{3} . ( \frac{senx}{cosx} ) ^{-1}   = \frac{2}{3} . tg x^{-1} =  \frac{2}{3} .  \frac{1}{2}  =  \frac{2}{6} =  \frac{1}{3}


Hipótese correta: B